Intra-operative recording of motor tract potentials at the cervico-medullary junction following scalp electrical and magnetic stimulation of the motor cortex. Issue 7 (July 1991) - Thompson, P D; Day, B L; Crockard, H A; Calder, I; Murray, N M; Rothwell, J C; Marsden, C D
Abstract : Activity in descending motor pathways after scalp electrical and magnetic brain stimulation of the motor cortex was recorded from the exposed cervico-medullary junction in six patients having trans-oral surgery of the upper cervical spine. Recordings during deep anaesthesia without muscle paralysis revealed an initial negative potential (D wave) at about 2 ms with electrical stimulation in five of the six patients. This was followed by a muscle potential which obscured any later waveforms. Magnetic stimulation produced clear potentials in only one patient. The earliest wave to magnetic stimulation during deep anaesthesia was 1-2 ms later than the earliest potential to electrical stimulation. Following lightening of the anaesthetic and the administration of muscle relaxants a series of later negative potentials (I waves) were more clearly seen to both electrical and magnetic stimulation. More I waves were recorded to magnetic stimulation during light anaesthesia than during deep anaesthesia. Increasing the intensity of electrical stimulation also produced an extra late I wave. At the highest intensity of magnetic stimulation the latency of the earliest potential was comparable to the D wave to electrical stimulation. The intervals between these various D and I waves corresponded to those previously described for the timing of single motor unit discharge after cortical stimulation.